DNA damage, inflammation, and cellular senescence investigation in SARS-CoV-2 infection: A short review - Kharisma, Viol Dhea; Ansori, Arif Nur Muhammad; Murtadlo, Ahmad Affan Ali; Turista, Dora Dayu Rahma; Tamam, Muhammad Badrut; Ullah, Md. Emdad; Jakhmola, Vikash (Genbinesia Journal of Biology, 2023)
SARS-2 infection is predicted to trigger DNA damage due to excessive inflammatory responses from the immune system such as cytokine storms. The cytokine storm leads to an increase in oxidative stress in cells, possibly triggering senescence through activation of the DNA damage response (DDR) signaling pathway. Alterations in the DDR pathway that induce cellular senescence have been identified due to the regulation of viral proteins that lead to impaired DNA repair. However, previous studies have not examined the relationship between DNA damage, inflammation, and cellular senescence. In this short review, we will discuss with a simple perspective why SARS-CoV-2 infection can accelerate the cellular senescence process and its relationship with the inflammatory response.